Political dynamics in knowledge work: using visual artifacts to deal with pragmatic boundaries - Comi, A; Vaara, E (INFORMS, 2021)
Previous research on knowledge work has started to explore how organizational actors deal with pragmatic boundaries that arise from their different interests, priorities, and viewpoints. Material objects, such as visual artifacts, can be used to shape and manipulate pragmatic boundaries, but our understanding of these dynamics is only partial. In this paper, we maintain that focusing on the uses of visual artifacts offers an opportunity to deepen our understanding of the political aspects of knowledge work. To this end, we conducted a practice-based study of an architectural project in which the building design became contested. Our empirical analysis reveals four practices in which visual artifacts are used to deal with pragmatic boundaries: surfacing, bridging, preventing, and minimizing. Through these practices, organizational actors can make boundaries more or less visible with important implications on their power relations and the project at hand. The main contribution of our study is to advance understanding of the political dynamics in knowledge work by revealing how visual artifacts can be used to manipulate pragmatic boundaries. By so doing, our analysis also helps to move the conversation on visual artifacts beyond their role as epistemic objects that sustain (or hinder) knowledge work.